Trump and West Asia: Policy Departures and Geopolitical Implications. (September 2018) - Quamar, Md. Muddassir
The first year and half of Trump's presidency has demonstrated a visible departure from the Obama's policy in West Asia. While the basic premise of the two administrations of protecting American national interest remains, their methods are significantly different. Obama wanted to move away while Trump has retrenched the USA in regional affairs. While Trump is being accused of taking rash decisions and pushing the region into further chaos, Obama's hands-off policy did not prevent the regional turmoil either. The common chord between Obama's legacy and Trump's policies in West Asia is that the USA is losing ground to emerging global powers, such as Russia and China despite remaining the predominant security guarantor.